Igualdade e cotas raciais - Costa, Rodrigo Moreira da (2017)
This dissertation focuses on the philosophical aspects of political and racial affirmative action programs adopted by our legal system. It will be analyzed the historical construction of the understanding of equality, and the beginning of its adoption in the legal systems. A parallel is due to be drawn between the positive and negative aspects of adopting affirmative action programs, in order to investigate the purpose conferred on its constitutionality before the principle of equality stamped in Article 5, caput, of our Constitution. In addition, the origin and use of such programs by the United States are seen as a comparative questioning the actual extensions of these programs in Brazil